Clinicopathological and prognostic significance of ubiquitin‐specific peptidase 15 and its relationship with transforming growth factor‐β receptors in patients with pancreatic ductal adenocarcinoma. Issue 2 (9th September 2020) - Jiang, Bolun; Zhou, Li; Lu, Jun; Wang, Yizhi; Liu, Chengxi; Liang, Zhiyong; Zhou, Weixun; You, Lei; Guo, Junchao
Abstract: Background and Aim: Ubiquitin‐specific peptidase 15 (USP15) has been correlated to aggressive oncogenic behavior in several types of carcinomas, but its function in pancreatic ductal adenocarcinoma (PDAC) has not been clarified. This study aimed to evaluate the clinicopathological and prognostic value of USP15 and its relationship with transforming growth factor‐β (TGF‐β) receptors (TβRs) in PDAC. Methods: By immunohistochemical staining of tissue microarrays, the expression patterns of USP15 and TβRs were retrospectively analyzed in 287 PDAC patients who underwent radical surgical resection without neoadjuvant therapy. Cancer‐specific survival was compared based on USP15 expression, and the correlations between USP15 and TβRs were analyzed. Results: Ubiquitin‐specific peptidase 15 expression in tumor tissues was significantly higher than that in para‐tumor tissues ( P  < 0.0001), and high USP15 expression was associated with the pathological N (pN) stage ( P  = 0.033). In addition, high USP15 expression was significantly associated with shorter cancer‐specific survival ( P  = 0.019). Univariate analyses showed that high USP15 expression ( P  = 0.024), a poor histopathological grade ( P  = 0.003), and the pN1 stage ( P  = 0.009) were significantly correlated with shorter survival. Although the independent prognostic value of USP15 alone was not established, the combination of USP15 and the histological grade was identified as an independent prognostic factor in multivariate analyses ( P  = 0.015). USP15 expression was correlated with TβR‐I, TβR‐II, or TβR‐III expression in PDAC. Conclusions: High USP15 expression is a potential prognostic indicator in patients with PDAC, and it might affect the TGF‐β signaling pathway in PDAC.